Asia in the making of Christianity : conversion, agency, and indigeneity, 1600s to the present - Young, Richard Fox; Seitz, Jonathan A. (Social sciences in Asia ;, 2013)
Asia in the Making of Christianity studies the experience of converts from fifteen locations throughout Asia, using a variety of approaches to examine the meaning of becoming Christian. The book addresses and assesses models under debate for understanding religious conversion.